Idee a problem natywizmu w filozofii Kartezjusza - Zbroszczyk, Wojciech (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2005)
According to Descartes ideas are the immediate objects of human mind. In "Meditationes de prima philosophia" there are three groups of ideas: "innatae", "adventitiae", "factae". However, in "Notae in Programma" Descartes says, that all human ideas must be innate. The ideas potentially exist in human mind. Descartes asserts human ideas are some kind of disposition to respond to sensory stimuli in particular way – by perceiving. The senses deliver occasions to actualizing our innate ideas. However, Descartes does not explain the way of actualizing of innate dispositions (ideas). This problem has not been resolved by now.